The power of GM-CSF: immune regulation in the defense against Phialophora verrucosa infection - Dong, Qi; Lu, Jiejie; Liu, Mengying; Wu, Weiwei; Kang, Yuying; Zhang, Ruijun (Frontiers in Immunology, 2025)
BackgroundPhialophora verrucosa, a dematiaceous fungus, causes serious infections such as phaeohyphomycosis. These infections can severely impair patient quality of life and may be life-threatening. Current understanding of host immune defenses against this pathogen remains limited.ObjectiveThis study aims to investigate the role of granulocyte-macrophage colony-stimulating factor (GM-CSF) in host defense against P. verrucosa. Using both in vivo and in vitro models, the current study specifically examines how GM-CSF deficiency impacts immune responses and fungal clearance.MethodsC57BL/6 wild-type (WT) and GM-CSF-deficient (Csf2 KO) mice were infected subcutaneously in the footpad with live P. verrucosa conidia. Skin lesion appearance and foot swelling were monitored for 4 weeks. At specific time points, footpad tissues were collected for PAS, CD68, and MPO staining, and colony-forming units were calculated to assess fungal load. Serum and tissue homogenates were analyzed for cytokine levels. Bone marrow-derived macrophages and neutrophils were isolated to evaluate GM-CSF’ s impact on chemotaxis, phagocytosis, and killing functions.ResultsCompared to WT mice, GM-CSF deficiency significantly delayed fungal clearance and prolonged disease progression, accompanied by reduced inflammatory responses and decreased neutrophil infiltration. In vitro, GM-CSF supplementation restored macrophage chemotaxis and enhanced neutrophil phagocytic activity, but did not affect their killing efficiency. A compensatory increase in IFN-γ levels in Csf2 KO mice was insufficient to overcome the immune defects caused by GM-CSF deficiency.ConclusionThis study reveals the indispensable role of GM-CSF in antifungal immunity and its potential as a therapeutic target for controlling infections caused by dematiaceous fungi.